2021
DOI: 10.3390/vision5010015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Perceptual Learning-Based Vision Training as an Adjuvant to Occlusion Therapy in the Management of Amblyopia: A Pilot Study

Abstract: A retrospective study was conducted to evaluate preliminarily the efficacy of perceptual learning (PL) visual training in medium-term follow-up with a specific software (Amblyopia iNET, Home Therapy Systems Inc., Gold Canyon, AZ, USA) for visual acuity (VA) and contrast sensitivity (CS) recovering in a sample of 14 moderate to severe amblyopic subjects with a previously unsuccessful outcome or failure with patching (PL Group). This efficacy was compared with that achieved in a patching control group (13 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…However, this does not mean that this active vision therapy is a substitute for patching [ 26 ]. Indeed, previous experiences have shown the benefit of the synergistic combination of patching and vision therapy, leading to satisfactory results, even in those cases treated unsuccessfully only with patching [ 18 , 27 ]. Likewise, the difference between the course of the treatment in strabismic and anisometropic amblyopia has been also demonstrated, with a slower recovery and the achievement of less degree of binocular vision in strabismic amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not mean that this active vision therapy is a substitute for patching [ 26 ]. Indeed, previous experiences have shown the benefit of the synergistic combination of patching and vision therapy, leading to satisfactory results, even in those cases treated unsuccessfully only with patching [ 18 , 27 ]. Likewise, the difference between the course of the treatment in strabismic and anisometropic amblyopia has been also demonstrated, with a slower recovery and the achievement of less degree of binocular vision in strabismic amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…Visual training using videogames and specific types of stimuli have been shown to be effective for improving visual function in different conditions [ 12 , 15 , 16 , 17 , 18 ], even in adult patients [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Specifically, the use of sinusoidal gratings with a neutral background can cause selective cortical responses for orientation and contrast [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These sessions will be 18 in total, will have an average duration of half an hour and will be distributed as follows: five sessions in the first week (Monday to Friday), three sessions in the second week (Monday, Wednesday and Friday) and a maintenance session in the following weeks (on Wednesdays). This is because it has been shown that most of the improvement obtained with visual training in amblyopia occurs during the first weeks of treatment [ 39 41 ]. Thus, patients assigned to group A will have to perform 10 sessions of active vision therapy with the NEIVATECH system during the first month of treatment, 4 during the second month and 4 during the third month.…”
Section: Methodsmentioning
confidence: 99%
“…Patient compliance with the NEIVATECH system will be determined by the number of sessions attended by each patient during the 3 months of the study, while compliance with the patch will be assessed by means of an adherence record to be completed by parents or legal guardians. Patient satisfaction and acceptance to the new therapy will be assessed using the User Satisfaction Evaluation Questionnaire (USEQ) [ 41 ] and the Technology Acceptance Model (TAM) questionnaire [ 42 ]. Finally, adverse reactions to therapy will be assessed using the standard and pediatric versions of the Simulator Sickness Questionnaire (SSQ) [ 43 , 44 ], depending on whether the patients are older or younger than 12 years of age.…”
Section: Methodsmentioning
confidence: 99%